PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAME TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV.C SD NEGERI 013 MEKAR SARI KOTA DUMAI TAHUN PELAJARAN 2013/2014 - Seri Rosdiana.D Rosdiana; Munjiatun '; Mahmud Alpusari Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This research based on the result of students learning outcomes of Science to the students IV.C SD Negeri 013 Mekar Sari. Based on the first observation, there are 5 students or 29% from 17 students achieved within minimum completeness criterion set in the school was 65. To improve students learning outcomes of Science, teacher used application coperative learning Method type TGT (Team Game Tournament). This reseach used classroom action research at fourth grade students SD Negeri 013 Mekar Sari within 17 students. This form of research is classroom action action research that consist of two cycles, each cycle consisting of planning, implementing, observation and reflection. Using data collection techniques observation and test. Data analysis techniques using statistics descriptive. To know improvement of learning outcomes of Science, it can be showed from frequence of students complete the passing grade. The initial result of learning outcomes of Science therea are 10 students within 59% completeness in UH I of cycle I and in UH II of cycle II, there are 16  students within 94% completeness. Base on the results of the study it can be concluded that the application of Cooperative Learning Method type TGT (Team Game Tournament) can improve students learning outcomes of Science Keywords  : Cooperative Learning Method, Type TGT, learning